Česká beseda v Liberci a česká menšina v 2. polovině 19. století - Šťovíček, Jan (Lidé města, 2000)
In the second half of the 19th century Liberec was considered as a center of Germans in Bohemia. Czechs, almost exclusively members of lower social strata, formed an ethnic minority there. After the fall of the Austrian neo-absolutism, in the situation of the initial development of association life in the monarchy, the Liberec Czechs established their association - česká beseda (1863). At the time of iits foundation it associated all strata of the Czech population in the town. However, soon after this, the workers started to distinguish themselves as they had their own specific political and social interests and approached internationally oriented German workers. From the very beginning česká beseda (Czech Popular Educational Association) was exposed to hostile power pressure by local Germans - the pressure was exerted at the community, professional as well as neighborly level. For all the pressures, thanks to the work of Česká beseda patriotic social life of the Czech Liberec was continually developing (theater, trips, singing, physical education). In 1881 Česká beseda prompted the foundation of a private Czech elementary school and in 1884 a public elementary school. In 1885 the local branch of Národní jednota severočeská (National North Bohemian Unity) and in 1886 a Sokol unit were founded. In 1890 thanks to the direct supported from Česká beseda a local branch of Klub českých turistů (Club of Czech Tourists) was founded. Czechs from Liberec established contacts with Czech associations in other towns of North Bohemia by means of Česká beseda's association activities. ln cooperation with other Czech associations Česká beseda was a major factor in the process of social and cultural emancipation of Liberec Czechs.